vault backup: 2025-02-16 18:47:21
This commit is contained in:
parent
acf45de160
commit
c2d96ec2e5
27
.obsidian/plugins/obsidian-git/data.json
vendored
27
.obsidian/plugins/obsidian-git/data.json
vendored
@ -1,27 +0,0 @@
|
|||||||
{
|
|
||||||
"commitMessage": "vault backup: {{date}}",
|
|
||||||
"autoCommitMessage": "vault backup: {{date}}",
|
|
||||||
"commitDateFormat": "YYYY-MM-DD HH:mm:ss",
|
|
||||||
"autoSaveInterval": 5,
|
|
||||||
"autoPushInterval": 0,
|
|
||||||
"autoPullInterval": 5,
|
|
||||||
"autoPullOnBoot": true,
|
|
||||||
"disablePush": false,
|
|
||||||
"pullBeforePush": true,
|
|
||||||
"disablePopups": false,
|
|
||||||
"listChangedFilesInMessageBody": false,
|
|
||||||
"showStatusBar": true,
|
|
||||||
"updateSubmodules": false,
|
|
||||||
"syncMethod": "merge",
|
|
||||||
"customMessageOnAutoBackup": false,
|
|
||||||
"autoBackupAfterFileChange": false,
|
|
||||||
"treeStructure": false,
|
|
||||||
"refreshSourceControl": true,
|
|
||||||
"basePath": "",
|
|
||||||
"differentIntervalCommitAndPush": false,
|
|
||||||
"changedFilesInStatusBar": false,
|
|
||||||
"showedMobileNotice": true,
|
|
||||||
"refreshSourceControlTimer": 7000,
|
|
||||||
"showBranchStatusBar": true,
|
|
||||||
"setLastSaveToLastCommit": false
|
|
||||||
}
|
|
@ -115,8 +115,13 @@ $$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
|||||||
|
|
||||||
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
||||||
1. First find the derivative of the outside function function ($f(x) = x^4$):
|
1. First find the derivative of the outside function function ($f(x) = x^4$):
|
||||||
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 $$
|
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$
|
||||||
2.
|
2. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
||||||
|
$$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
||||||
|
> Apply the chain rule to $x^4$
|
||||||
|
|
||||||
|
If we treat the above as a function along the lines of $f(x) = (x)^4$, and $g(x) = x$, then the chain rule can be used like so:
|
||||||
|
$$ 4(x)^3 * x $$
|
||||||
# Trig Functions
|
# Trig Functions
|
||||||
$$ \lim_{x \to 0} \dfrac{\sin x}{x} = 1 $$
|
$$ \lim_{x \to 0} \dfrac{\sin x}{x} = 1 $$
|
||||||
$$ \lim_{x \to 0} \dfrac{\cos x - 1}{x} = 0 $$
|
$$ \lim_{x \to 0} \dfrac{\cos x - 1}{x} = 0 $$
|
||||||
@ -149,8 +154,8 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$
|
|||||||
|
|
||||||
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
||||||
|
|
||||||
3. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
2. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
||||||
4. $= 4x^\frac{1}{3} - x^{-6}$
|
3. $= 4x^\frac{1}{3} - x^{-6}$
|
||||||
5. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
4. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
||||||
6. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
5. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
||||||
7. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$
|
6. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$
|
Loading…
x
Reference in New Issue
Block a user